Experimental-numerical investigation of rotor-rotor aerodynamic interactions for eVTOL aircraft configurations - Piccinini, R.; Tugnoli, M.; Zanotti, A. (My University, 2020)
The paper presents the description of a research activity aimed to the systematic study of the rotor-rotor aerodynamic interaction with application to the flight conditions typical of eVTOL aircraft. The activity considers a dual effort, experimental and numerical, to gather systematic parametric data on different types of rotor-rotor interactions. In particular, the paper describes the planning and set up of a wind tunnel campaign aimed to evaluate the effects of the aerodynamic interactions on the rotor performance and flow field for two propeller models both in side-by-side and tandem configuration. Moreover, the results of numerical simulations performed with a mid-fidelity aerodynamic code on both the planned test configurations are presented showing the main effects of the aerodynamic interactions on the performance of the propeller.